Elite national athletes reach their peak performance later than non-elite in sprints and throwing events - Boccia, G.; Brustio, P. R.; Moisè, P.; Franceschi, A.; La Torre, A.; Schena, F.; Rainoldi, A.; Cardinale, M. (Journal of Science and Medicine in Sport, 2019)
Objectives: The aim of this study was to describe and analyse the performance career trajectories for Italian athletes that participated in sprint, hurdles, discus throw, and shot-put athletics events. Design: Retrospective study, data collected between 1994 and 2014. Methods: A total of 5929 athletes (female: n = 2977, 50.2%) were included in the study. The age of entering competition and personal best performance was identified in the official competition records. Personal best performances were ranked in percentiles and top-level athletes were considered those in the highest 4% of the performance distribution. Results: Overall, when controlling for the age of entering competition, top-level athletes reached their personal best later (i.e., around 23-25 years old) for all events compared to the rest of the athletes. Moreover, regression analysis showed that entering competitions later was linked to better performances during adulthood. Also, only 17%-26% [90% CI] of the top-level adult athletes were considered as such when they were 14-17 years old. Conclusions: Together, these findings suggest that early sport success is not a strong predictor of top-level performance at senior level. Entering sport-specific competitions later and lengthening the sports career at beyond 23-25 years of age may be important factors to reach top-level performance in sprint and throwing events.